Selective inhibition of cytosine-DNA methylases by polyamines - Ruiz-Herrera, J.; Ruiz-Medrano, R.; Dominguez, A.
We have advanced the hypothesis that polyamines affect DNA methylation and thus promote the expression of developmentally controlled genes. We demonstrate that the activity of cytosine-DNA methyltransferases HpaII, HhaI, HaeIII and SssI is inhibited by physiological concentrations of polyamines. On the other hand, activity of the adenine-DNA methyltransferase EcoRI, and restriction enzymes HpaII, HhaI, HaeIII and EcoRI, is insensitive to polyamine concentrations up to 40 mM. Our results indicate that the effect of polyamines on cytosine- DNA methyltranferases is rather selective and suggest a possible mode of action in vivo.
Keywords: PUTRESCINE; SPERMIDINE; DNA-METHYLATION; RESTRICTION ENZYME